2010
DOI: 10.1002/ana.21831
|View full text |Cite
|
Sign up to set email alerts
|

Local institutional review board (IRB) review of a multicenter trial: Local costs without local context

Abstract: Multicenter clinical research involves parallel IRB reviews based on the premise that local review reflects aspects of the research environment. We examined the costs and effects of local IRB review of the consent and protocol in a multicenter clinical trial in Parkinson's disease. Seventy six percent of changes to the consent reflected standard institutional language, with no substantive changes to the protocol. The costs of this process exceeded $100,000. These findings support initiatives by the Office of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…Despite great interest, enrollment in the study took 13 months, principally due to the need for review and approval of the protocol by each site's institutional review board. The limitations of local institutional review board review in multicenter studies, [54][55][56] as well as the benefits of central institutional review boards, have been well documented. [57][58][59][60][61] The other principal source of delay was the requirement for hand-signed consent forms, which could be addressed by adopting the electronic signatures that are increasingly used in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Despite great interest, enrollment in the study took 13 months, principally due to the need for review and approval of the protocol by each site's institutional review board. The limitations of local institutional review board review in multicenter studies, [54][55][56] as well as the benefits of central institutional review boards, have been well documented. [57][58][59][60][61] The other principal source of delay was the requirement for hand-signed consent forms, which could be addressed by adopting the electronic signatures that are increasingly used in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 90% of sites used their local IRB, whereas a CIRB system may have speeded up the approval process by eliminating duplication of efforts at local sites. 15 For multicenter clinical trials in Parkinson disease, Ravina et al 15 reviewed the impact of local IRB reviews on safety and costs and found that local IRB reviews did not result in any significant changes to the protocol, and that these minor changes made no difference to a person's decision to participate in a trial. In addition to start-up delays, the cost of this process exceeded $100,000.…”
Section: Adherence and Retentionmentioning
confidence: 99%
“…In addition to start-up delays, the cost of this process exceeded $100,000. 15 Implementation of a CIRB model in oncology trials was associated with faster review and less IRB staff effort. 17 The main mission of the IRB is to protect the welfare of study participants; however, the prolonged IRB approval timelines contribute to inflating the cost of clinical trials and delaying finding treatments for people with devastating diseases such as ALS.…”
Section: Adherence and Retentionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Taken together, the procedural inefficiency, inconsistency, high administrative burden and increasing cost of the ethics approval process under the institution-by-institution model prompted transition to a single institutional review board (sIRB) approach for multi-site studies within the United States by 2020 1 and in other international jurisdictions. [28][29][30] The sIRB model is purported to better respond to the contemporary realities and practices of collaborative, data-intensive research typified by the emerging 'omics' disciplines.…”
Section: Clinical Research and Health Information Data Sharing Are Bumentioning
confidence: 99%